Validating self-reported Toxic Release Inventory data using Benford's Law: investigating toxic chemical release hazards in floodplains - Osiecki, Kristin; Hussaini, Syed; Sambanis, Apostolis; Quinsey, Logan; Liew, Chloe (Frontiers in Public Health, 2024)
Acute and long-term health impacts from flooding related toxic chemical releases are a significant local health concern and can disproportionately impact communities with vulnerable populations; reliable release data are needed to quantify this hazard. In this paper, we analyze US Federal Emergency Management Agency designated floodplain data and US Environmental Protection Agency Toxic Release Inventory (TRI) data to determine if geographically manipulated databases adhere to Benford's Law and thereby validate the self-reported toxic release dataset. We find that Benford's Law applies to self-reported toxic chemical release and disposal data, indicating a lack of widespread data errors or manipulation. It relates directly to understanding the environmental health concerns posed to public health regarding flooding incidents.